2019
DOI: 10.3847/2041-8213/ab54d1
|View full text |Cite
|
Sign up to set email alerts
|

Anomalously Narrow Line Widths of Compact Massive Star-forming Galaxies at z ∼ 2.3: A Possible Inclination Bias in the Size–Mass Plane

Abstract: Compact, massive star forming galaxies at z ∼ 2.5 are thought to be building the central regions of giant elliptical galaxies today. However, a significant fraction of these objects were previously shown to have much smaller Hα line widths than expected. A possible interpretation is that Hα emission from their central regions, where the highest velocities are expected, is typically obscured by dust.Here we present ALMA observations of the CO(3-2) emission line of three compact, massive galaxies with Hα line wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
3
6
0
Order By: Relevance
“…In Figure 14, we recreate this relationship using both the light and mass semimajor axes. We find a similar correlation to Mowla et al (2019b) between the semimajor axis and axis ratio. For mass radii, there is much less correlation.…”
Section: Physical Drivers Of the Color Gradientssupporting
confidence: 71%
See 1 more Smart Citation
“…In Figure 14, we recreate this relationship using both the light and mass semimajor axes. We find a similar correlation to Mowla et al (2019b) between the semimajor axis and axis ratio. For mass radii, there is much less correlation.…”
Section: Physical Drivers Of the Color Gradientssupporting
confidence: 71%
“…Related to this is the issue of an inclination bias in the sizemass plane, as suggested by Mowla et al (2019b). The authors investigate a discrepancy between the observed line width and that expected by simple viral estimator for three compact starforming galaxies.…”
Section: Physical Drivers Of the Color Gradientsmentioning
confidence: 97%
“…Finally, we note that our size measurements for these dusty star-forming galaxies do not appear to be driven by observational biases. First, inclination bias does not seem to play an important role: the observed axis ratios of the compact and extended z > 2 dusty star-forming galaxies do not differ significantly (though see Mowla et al 2019). Second, our methods appear able to accurately recover the half-mass radii of dusty star-forming galaxies despite their highly dust-obscured centers.…”
Section: Dusty Star-forming Galaxiesmentioning
confidence: 81%
“…This is comparable to the velocity dispersion measured from the stellar absorption lines (88 ± 18 km/s, Belli et al 2014), but significantly lower than the value expected for a pressuresupported system, which is σ virial > 130 km/s (this is a lower limit obtained by neglecting the dark matter contribution). The most likely explanation for this discrepancy is that both the stellar and the molecular gas content are distributed in a nearly face-on rotating disk, which is also consistent with the circular morphology of the galaxy (see Mowla et al 2019 for similar cases). Such alignment suggests that the molecular gas reservoir was formed together with the stellar content, and is not a product of recent accretion.…”
Section: Co Emission and Molecular Gas Massesmentioning
confidence: 52%